The concept of person understood as participation in the Love of the Holy Trinity. Orthodox Perspective - Brînzea, Nicolae; Ciucă Bancu, Cosmin (Technium Social Sciences Journal, 2022)
The concept of person is often defined from the perspective of how the humanities understand it. Interestingly, no science has succeeded in a complete definition of the person, precisely because of the complexity of the soul with which God endows man. Thus, if the sciences without reference to God transform the person into an individual, from a theological perspective the two terms have a completely different meaning. This results from the correct relationship of man to God, a relationship that has the effect of knowing the happiness of man, happiness to which he tends through creation.